Malawi gender strategy: Building equitable climate-resilient African bean & insect sectors - Kabuli, Hilda; Ouya, Frederick; Chisale, Virginia; Kachigamba, Donald; Chakhumbira, Feston; Botha, Sara; Lutomia, Cosmas; Ketema, Dessalegn; Nchanji, Eileen (2025)
The Building Equitable Climate-Resilient African Bean and Insect Sectors (BRAINS) project is a multi-country initiative that aims to create low-carbon, climate-resilient, and inclusive agricultural systems across 15 nations in sub-Saharan Africa. In Malawi, BRAINS focuses on strengthening the bean, fruit-tree (mango and avocado), beekeeping and insects-for-food-and-feed value chains while mainstreaming gender equality so that women, youth and other marginalised groups both participate in and benefit from climate-resilient agricultural transformation (Kabuli et al., 2025). Malawi’s agricultural sector remains the backbone of rural lives and national food security but is highly exposed to climate variability, reflected in periodic droughts, floods and pest outbreaks that impair smallholder production and incomes (Government of Malawi, 2016a; 2016b). These climatic challenges reinforce longstanding gender inequalities: women undertake a major share of agricultural labour but generally have less access than men to land, finance, extension, improved inputs, and high-value market outlets (World Bank, 2024; UN Women/ AfDB, 2020). The BRAINS baseline quantitative analysis conducted in Nkhotakota and Mwanza districts of Malawi documents these patterns in detail. Men have bigger landholdings and have more access to extension services and formal market channels, whereas women are disproportionately involved in subsistence production, free labour, local markets, and have lower digital access for agro-weather information services, limiting their capacity to adopt climate-smart technologies and to control benefits from these value chains (Kabuli et al., 2025). Female-headed rural households often lose comparatively more income during catastrophic weather events and face systemic impediments in obtaining adaptive finance, technologies and information (FAO, 2024). Gender disparities in land rights and asset ownership also impede women’s ability to invest in long-term, climate-resilient assets such as perennial fruit trees and beekeeping infrastructure (FAO, 2011; World Bank, 2024). This Malawi Gender Strategy responds to these challenges by establishing a structured and evidence-based framework for mainstreaming gender equality and social inclusion throughout all BRAINS activities. It builds on the reach, benefit, empower, and transform framework to ensure that vulnerable and marginalised groups including women, youth, persons with disabilities are not only reached by project activities, but also benefit equitably, gain agency, and contribute to transforming the norms, systems, and institutions that perpetuate inequality.